Methods of intervention in the control of ragweed spread (Ambrosia artemisiifolia L.) in the area of Zagreb County and the city of Zagreb - Gajnik, Davorin (Array, 2009)
Abstract: The increase in ragweed mediated health problems has led to the development of defense strategies in the countries with the most serious ragweed pollution, namely Hungary, Italy and France. The aim of this paper is to define the frequency of allergic disturbances brought by ragweed pollen in the period between 2002 and 2004, and to devise an action plan for its eradication in the area of Zagreb, as well as in Zagreb County. Thanks to the analysis of common methods of ragweed eradication, even by stating biological ragweed eradication, the best efficiency in ragweed eradication would be achieved through a method that combines several common methods, i.e. a mixed method. In its order on taking measures for obligatory eradication of ragweed, it has stated that the Ministry will ensure funds so that Plant Protection Department in Agriculture and Forestry of the Republic of Croatia, and Department of Herbology of the Faculty of Agriculture of Zagreb could observe the beginning and continuity of ragweed blossom, make an evaluation on the degree of weed overgrowth, establish how widespread it is in the Republic of Croatia, inform the public via the media on control measures and some other duties, but there is no financial help to those who are selected to eradicate ragweed